2019
DOI: 10.1002/anie.201904102
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Chemoenzymatic Synthesis of (−)‐Podophyllotoxin and Related Aryltetralin Lignans

Abstract: À)-Podophyllotoxin is one of the most potent microtubule depolymerizing agents and has served as an important lead compound in antineoplastic drug discovery. Reported here is as hort chemoenzymatic total synthesis of (À)-podophyllotoxin and related aryltetralin lignans.V ital to this approach is the use of an enzymatic oxidative C À C coupling reaction to construct the tetracyclic core of the natural product in ad iastereoselective fashion. This strategy allows gram-scale access to (À)-deoxypodophyllotoxin and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 39 publications
0
44
0
Order By: Relevance
“…379 Recently, both Fuchs et al and Renata et al have independently employed the dioxygenase from Podofyllum hexandrum (2-ODD-PH) to achieve the synthesis of podophyllotoxin itself. 380,381 Multigram scale resolution of racemic hydroxy-yatein (300) through selective conversion of (À)-hydroxy-yatein to epipodophyllotoxin (epi-299) using 2-ODD-PH had been shown by Fuchs and co-workers (Scheme 60B). Subsequent chemical steps furnished podophyllotoxin (299) in 32% overall yield.…”
Section: Scheme 59mentioning
confidence: 99%
“…379 Recently, both Fuchs et al and Renata et al have independently employed the dioxygenase from Podofyllum hexandrum (2-ODD-PH) to achieve the synthesis of podophyllotoxin itself. 380,381 Multigram scale resolution of racemic hydroxy-yatein (300) through selective conversion of (À)-hydroxy-yatein to epipodophyllotoxin (epi-299) using 2-ODD-PH had been shown by Fuchs and co-workers (Scheme 60B). Subsequent chemical steps furnished podophyllotoxin (299) in 32% overall yield.…”
Section: Scheme 59mentioning
confidence: 99%
“…[197][198][199] Chemoenzymatic approaches have also proved useful in the synthesis of natural products. [200][201][202][203] A recent important publication by Lipshutz and coworkers has shown that the formation of micelles in the reaction medium can facilitate the combination of chemo-and bio-catalysis in a single reactor as the substrates, products and catalysts partition into the different compartments. 204 For an extensive review of the recent literature on biocatalytic cascade reactions see Kroutil and coworkers.…”
Section: Integration: Biocatalytic and Chemoenzymatic Cascade Processesmentioning
confidence: 99%
“…In order to illustrate more broadly the biocatalytic potential of Fe/KGs, it is also imperative that we show their utility in the synthesis of other natural-product families as well. To this end, our laboratory has recently made headway in showcasing the application of two Fe/KGs, 2-ODD-PH and PtmO6, in the chemoenzymatic total synthesis of the aryltetralin lignans (Scheme 5C) 68 and oxidized ent-kauranes (Scheme 5D), 69 respectively. Efforts from other laboratories 70 have also asserted the general utility of this enzyme superfamily in organic synthesis.…”
Section: Account Synlettmentioning
confidence: 99%